THE ROLE OF TAHFIZ TEACHERS IN IMPROVING QURANIC MEMORIZATION: A CASE STUDY OF STUDENTS AT MA’HAD TAHFIZ IMAM AHMAD ABI ABDILLAH ISLAMIC BOARDING SCHOOL - tharra yasmin lubis; Koko khoerudin (Atta'dib Jurnal Pendidikan Agama Islam, 2026)
This study examines the role of tahfiz teachers in enhancing students' Quranic memorization at Ma'had Tahfiz Imam Ahmad Abi Abdillah, driven by the intensive target of memorizing 30 juz within two years. Utilizing a qualitative field research design, data were gathered through in-depth interviews and direct observations. The primary subject was the tahfiz teacher (ustadzah), focusing on her instructional strategies, assistance, and monitoring mechanisms. Data were analyzed using reduction, data display, and conclusion drawing. The findings reveal that the teacher fulfills four critical roles: guide, motivator, role model, and evaluator. The ustadzah effectively facilitates new memorization (sabak), reinforces recent memorization (murojaah), sustains motivation during cognitive fatigue, exemplifies disciplined Islamic character, and conducts rigorous daily and periodic assessments. Synchronously, these roles foster an integrated, holistic, and effective learning environment. This study concludes that students' success in accelerated Quranic memorization relies heavily on comprehensive pedagogical guidance that synthesizes academic instruction, psychological motivation, exemplary behavior, and continuous evaluation.